Role of biogas technology adoption in forest conservations: evidence from Ethiopia - Yadeta Bekele Bekere; Guta Regasa Megerssa (Journal of Degraded and Mining Lands Management, 2020)
Almost all developing countries satisfy their energy requirements from firewood. In Ethiopia majority of the rural population relies on biomass energy sources for every energy necessities. Fuelwood accounts for about 78 % of the total energy needs, whereas animal dung and crop residue share 12 % and nine percent, respectively. Almost all of the firewoods are collected from natural forests and few of them from homestead trees. Chronic drought, land degradation, and loss of soil fertility that are positively correlated with low livestock and crop productivity are extensions of deforestation for firewood. Heavy dependency on biomass fuel in Ethiopia has resulted in fast deforestation, desertification, climate change, global warming and finally decrease in agricultural productivity. Therefore the adoption of biogas technologies has great potentials to supply low-cost energy and results in less dependency on firewood. To improve such adverse socio-economic and ecological costs, interventions like improved biogas technologies, raising community awareness on deforestation, and utilization of alternative energy technologies are recommended to conserve natural forests.